MODAL SOSIAL TERHADAP KETAHANAN KELOMPOK PEREMPUAN PADA USAHA MIKRO KECIL MENENGAH TERMINAL WARUMUSIO KOTA BAUBAU - Wa Ode Sunarli; LM.Azhar Sa’ban; Andi Arya Maulana Wijaya; Fitriani Abbas (Governance, 2024)
In crisis conditions, social capital has a positive impact on the resilience of Micro, Small and Medium Enterprises (MSMEs). However, this group becomes vulnerable due to various changes in the local economy, including MSME actors from the Women's Group. Therefore, it is important to ensure their resilience through its social capital elements. This study aims to describe the social capital elements of women's groups in the context of MSME actors, especially in the Warumusio Terminal area of Baubau City. This research uses a type of qualitative research, which is conducted through a descriptive approach. The determination of research informants was carried out through purposive sampling assisted by snowball sampling to find the uniqueness of the group's social capital, so that informants were selected from MSME groups, the Village Government and several relevant stakeholders. Furthermore, the data were analyzed through qualitative analysis rules and presented descriptively and systematically in explaining the typology of each element of social capital. This study found that the social capital of Warumusio Terminal MSMEs inwardly is stronger than outward social capital, so that the vulnerability of the group can be identified from the way the group builds cooperation networks with other groups. Therefore, in the context of MSMEs Warumusio Terminal social capital such as trust, norms and cooperation is effective. This research suggests that building the resilience of women's groups in MSME actors can be done through empowerment based on institutional strengthening and cooperation.